Nickel-based alloy and preparation method thereof
By adding yttrium and niobium to the nickel-based alloy and adjusting its microstructure, the problem of insufficient mechanical properties of existing molten salt stack structural materials at high temperatures is solved, and the tensile strength, yield strength and elongation are significantly improved, ensuring melting Salt heaps are safe and efficient in operation.
Patent Information
- Application Number
- CN202411577168.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult for existing molten salt pile structural materials to maintain long-term stable mechanical properties at high temperatures, especially at temperatures of 700°C and above, and the tensile strength and yield strength are insufficient, which affects the safety and operating efficiency of molten salt piles.
By adding 0.02%-0.08% yttrium and 0-1.54% niobium to the nickel-based alloy, the microstructure of the alloy is adjusted to significantly improve its high-temperature mechanical properties.
The tensile strength, yield strength and elongation of nickel-based alloys at 700℃-800℃ are significantly improved, ensuring the long-term stable performance of structural materials at high temperatures, and enhancing the safety and operating efficiency of molten salt piles.
Smart Images

Figure CN119464843A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an alloy, and more particularly to a nickel-based alloy and a preparation method thereof. Background Art
[0002] Molten salt reactors use molten mixed salts as coolants, which have good safety performance and unique advantages such as high temperature and low pressure. In molten salt reactors, fuel carrier salts and cooling salts usually contain fluoride salts of Li, Be, Na, Zr, and K. These molten salts will directly enter the heat exchanger system for heat exchange during the operation of the reactor. Since the wall thickness of the heat exchanger is only 1-2 mm, the alloy used as the structural material of the heat exchanger must have good high temperature strength, high temperature molten salt corrosion resistance, and neutron irradiation resistance at high temperatures of 600-700°C. Comprehensive material performance evaluation shows that a major technical difficulty of high temperature molten salt reactors is whether the structural materials can have long-term stable mechanical properties in a high temperature molten salt environment. For high temperature molten salt reactors, the increase in operating temperature can greatly improve the operating efficiency of the reactor, and the service temperature of the structural material is the key factor in determining the operating temperature of the molten salt reactor.
[0003] UNS N10003 (Hastelloy N) alloy is a widely used structural material for molten salt reactors, and its maximum allowable temperature is 704°C. However, in order to adapt to the higher operating temperature of molten salt reactors, it is necessary to develop new alloy materials with better high-temperature mechanical properties. The current operating temperature of molten salt reactors is 650°C. At the reactor operating temperature, we hope that the structural materials have better tensile strength, enough to withstand the problems faced in the working environment. In order to meet the demand for structural materials for molten salt reactors operating at higher temperatures in the future, it is hoped that the structural alloy materials used will have higher tensile strength and yield strength, especially structural alloy materials with higher tensile strength at 700°C and higher yield strength at 800°C, so as to ensure the safety of molten salt reactors in long-term service. Summary of the invention
[0004] In order to improve the high temperature mechanical properties of nickel-based alloys to meet the use requirements of structural materials for molten salt reactors with higher operating temperatures in the future, the present invention provides a nickel-based alloy and a preparation method thereof.
[0005] According to the nickel-based alloy of the present invention, it includes the following weight percentage components: 0.02%-0.08% yttrium, 0-1.54% niobium, 6.91%-7.10% chromium, 12.00%-16.45% molybdenum, and the balance of nickel and inevitable impurities. Adding an appropriate amount of yttrium and niobium to the alloy can effectively change the microstructure of the alloy and significantly improve the high-temperature mechanical properties of the alloy. It should be understood that the addition of excessive yttrium and niobium will lead to the formation of harmful phases in the alloy, thereby affecting the alloy structure and the final high-temperature mechanical properties.
[0006] In a preferred embodiment, the nickel-based alloy includes the following components in weight percentage: 0.06%-0.08% yttrium, 7.10% chromium, 13.00%-16.45% molybdenum, the balance of nickel and inevitable impurities. Rare earth yttrium can effectively purify the grain boundaries of the alloy and improve the grain boundary strength, so that the grain boundaries and grains are adapted during the deformation process, avoiding the premature generation of grain boundary cracks, thereby improving the high temperature strength of the alloy and also well improving the elongation of the alloy.
[0007] In a preferred embodiment, the nickel-based alloy includes the following components in weight percentage: 0.08% yttrium, 7.10% chromium, 16.45% molybdenum, the remainder nickel and inevitable impurities. 0.08wt% yttrium element significantly improves the high temperature tensile strength of the alloy at 700°C and 800°C, and the elongation is also greatly improved.
[0008] In a preferred embodiment, the nickel-based alloy includes the following components in weight percentage: 0.02%-0.04% yttrium, 1%-1.54% niobium, 7.10% chromium, 12.00%-13.00% molybdenum, and the balance of nickel and inevitable impurities. Since niobium can effectively improve the alloy's radiation resistance and tellurium embrittlement resistance, when niobium is added to the alloy, niobium carbide will precipitate in the alloy, thereby improving the alloy's properties.
[0009] In a preferred embodiment, the nickel-based alloy includes the following components in weight percentage: 0.02% yttrium, 1.54% niobium, 7.10% chromium, 12.00% molybdenum, the balance of nickel and inevitable impurities. When the temperature is increased to 800°C, the improvement of adding niobium and yttrium at the same time is better, including yield strength and elongation. Specifically, the dispersed fine niobium carbide can not only improve its strength, but also improve the radiation resistance and tellurium embrittlement resistance of the alloy. However, at high temperatures greater than 700°C, niobium carbide is easy to grow and decompose, and rare earth yttrium can hinder its growth, thereby further preventing its decomposition, so that the niobium-based alloy can be used at higher temperatures. However, when the molybdenum content in the alloy is 16wt%, M6C-type Mo-rich carbides are mainly precipitated in the alloy, and it is difficult to form niobium carbide in the alloy, so the alloy with niobium added should reduce the molybdenum content in the alloy. At the same time, it is important that reducing the molybdenum content can effectively reduce the manufacturing cost of the alloy. Therefore, on the basis of the UNS N10003 composition, reducing the molybdenum content in the alloy to about 12wt%, adding 1.54wt% niobium, and adding 0.02wt% rare earth yttrium can effectively improve the high temperature strength and elongation of the alloy, achieving the same or even better high temperature strength and elongation as the alloy with only yttrium added.
[0010] In a preferred embodiment, the nickel-based alloy further comprises 0.012%-1.6% iron, 0.35%-0.38% silicon, 0.65%-0.67% manganese, and 0.04% carbon in weight percentages.
[0011] In a preferred embodiment, the impurities are sulfur, boron, and phosphorus at a weight percentage of less than 50 ppm.
[0012] The method for preparing the nickel-based alloy according to the present invention comprises smelting, homogenization treatment and forging treatment in sequence.
[0013] In a preferred embodiment, the temperature of the homogenization treatment is between 1150° C. and 1180° C., and the time of the homogenization treatment is between 2 h and 10 h.
[0014] In a preferred embodiment, the initial forging temperature of the forging process is 1160°C, and the final forging temperature of the forging process is 1100°C.
[0015] According to the nickel-based alloy and the preparation method thereof of the present invention, by adding yttrium with a weight ratio of 0.02%-0.08% and niobium with a weight ratio of 0-1.54%, the high-temperature mechanical properties of the alloy at 700°C-800°C are effectively improved. Compared with the Ni-16.35Mo-7.1Cr high-temperature alloy, it has higher tensile strength (554.3Mpa-538.65MPa), yield strength (233.4MPa-244.0MPa) and elongation (48.7%-56.8% at 700°C, 68.5%-80.3% at 800°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 2 are microstructure diagrams of the embodiments of the present invention and the comparative examples after homogenization and after forging.
[0017] Figure 2 It is a relationship curve diagram between the yttrium / niobium content in the nickel-based alloy according to the embodiment of the present invention and the comparative example and the high temperature mechanical properties at 700°C.
[0018] Figure 3 The SEM morphology of the fracture surface of the nickel-based alloy 700°C high temperature tensile test specimens according to the embodiments of the present invention and the comparative example.
[0019] Figure 4 The SEM morphology diagrams of the cross-section cracks of the nickel-based alloy 700° C. high-temperature tensile specimens according to the embodiments of the present invention and the comparative examples are shown.
[0020] Figure 5 It is a relationship curve diagram between the yttrium / niobium content in the nickel-based alloy according to the embodiment of the present invention and the comparative example and the high temperature mechanical properties at 800°C.
[0021] Figure 6The SEM morphology of the fracture surface of the nickel-based alloy 800° C. high temperature tensile test specimens according to the embodiments of the present invention and the comparative example.
[0022] Figure 7 The SEM morphology diagrams of the cross-section cracks of the nickel-based alloy 800° C. high-temperature tensile specimens according to the embodiments of the present invention and the comparative examples are shown.
[0023] Figure 8 This is a high-magnification cross-sectional morphology image of the nickel-based alloy according to Example S2 of the present invention after high-temperature stretching at 800°C. DETAILED DESCRIPTION
[0024] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.
[0025] The preparation method of the nickel-based alloy of Comparative Example S0 and Examples S1 and S2 of the present invention first includes smelting. Specifically, the smelting is performed in a vacuum induction melting furnace, and the alloy is subjected to impurity removal treatment in a vacuum consumable melting furnace.
[0026] The preparation method of the nickel-based alloy of the comparative example S0 and the examples S1 and S2 of the present invention then includes a homogenization treatment. Specifically, the temperature of the homogenization treatment is between 1150°C and 1180°C, and the time of the homogenization treatment is between 2h and 10h according to the size of the sample, and the reference homogenization time is based on 2 mm / hour.
[0027] The preparation method of the nickel-based alloy of the comparative example S0 and the examples S1 and S2 of the present invention then includes a forging process. In one embodiment, the initial forging temperature of the forging process is 1160° C., and the final forging temperature of the forging process is 1100° C. In one embodiment, the deformation amount is 80%.
[0028] The present invention is committed to developing a nickel-based alloy with performance that exceeds that of Ni-16.35Mo-7.1Cr high-temperature alloy. It has more excellent high-temperature mechanical properties and can better meet the needs of structural materials for future molten salt reactors. Therefore, the properties of particular concern are the tensile properties and elongation of the alloy at 700°C and the yield strength and elongation at 800°C. Comparative Example S0 is UNSN10003 alloy, i.e. Ni-16.35Mo-7.1Cr. Examples S1 and S2 add trace amounts of yttrium and niobium and reduce the molybdenum content on the basis of Comparative Example S0. The chemical compositions of the three alloys are shown in Table 1 below.
[0029] Table 1 Chemical composition of alloys in Examples and Comparative Examples
[0030] The microstructures of the three nickel-based alloys S0, S1, and S2 after homogenization and forging were etched by aqua regia. Figure 1As shown in the figure, after the alloy was homogenized at 1150℃ for 10 hours, the dendrite structure was completely eliminated, and a large-sized columnar crystal structure was presented, and uniformly distributed black dot-shaped precipitated carbides (Nb and / or Mo carbides) appeared in the alloy. The grain size decreased as the yttrium content increased. After high-temperature forging at 1160℃ and a rolling amount of 70%-80%, the structure was transformed into uniform equiaxed grains, and the grains were significantly finer than the homogenized columnar crystal structure; the uniformly distributed black structure in the alloy was the carbides precipitated after forging.
[0031] The three nickel-based alloys S0, S1 and S2 were processed into specimens and subjected to high-temperature tensile tests at 700℃ and 800℃ respectively.
[0032] The results of 700℃ high temperature tensile test of three nickel-based alloys S0, S1 and S2 are shown in Figure 2 As shown. Compared with the comparative example S0 alloy, the tensile strength (fracture resistance) of the example S1 and S2 alloys is significantly improved, and the elongation is greatly improved. The tensile strength is increased from 512.95MPa in the comparative example S0 to 554.3MPa in the example S1 and 538.65MPa in the example S2, respectively. The elongation is increased from 34.95% in the comparative example S0 to 48.7% in the example S1 and 56.8% in the example S2, respectively.
[0033] The fracture morphology of the three nickel-based alloys S0, S1, and S2 at 700℃ is shown in Figure 2. Figure 3 As shown, dimples appear at the fracture of the comparative example S0 and the examples S1 and S2, but the dimples of the comparative example S0 are larger and have larger cracks and obvious intergranular fractures, while the dimples of the examples S1 and S2 are finer and denser and have no intergranular fractures, and are very uniform overall.
[0034] The cracks of the 700℃ high temperature tensile cross section of three randomly selected locations of three nickel-based alloys S0, S1, and S2 are shown in Figure 2. Figure 4 As shown. While the elongation of the alloys of Examples S1 and S2 is improved, the cracks in the alloys are not obvious, indicating that the alloys have excellent toughness and ductility. In addition, compared with the comparative example S0, the number of cracks in the cross-section of the tensile specimens of Examples S1 and S2 is significantly reduced and the crack length is significantly shortened, showing a better anti-cracking ability.
[0035] The results of 800℃ high temperature tensile test of three nickel-based alloys S0, S1 and S2 are shown in Figure 5As shown. The yield strength of Example S1 and S2 alloys is significantly improved compared with the comparative example S0 alloy, and the elongation is greatly improved. The yield strength is increased from 226.8MPa in comparative example S0 to 233.4MPa in Example S1 and 244.0MPa in Example S2, respectively. The elongation is increased from 43.9% in comparative example S0 to 68.5% in Example S1 and 80.3% in Example S2, respectively. In particular, while the yield strength (resistance to plastic deformation) of Example S1 is improved, the elongation is also greatly improved, avoiding the irreversible consequences brought about by the sudden fracture of the structural materials used in the stack, which is crucial to the safe operation of the stack.
[0036] The fracture morphology of three nickel-based alloys S0, S1, and S2 at 800℃ high temperature tensile test is shown in Figure 2. Figure 6 As shown, the comparative example S0 has obvious intergranular cracking and almost no dimples are generated, while the examples S1 and S2 have no obvious intergranular fracture and evenly distributed dimples appear, and the dimples of S1 are more fine and dense.
[0037] The cross-sectional cracks of three randomly selected locations of three nickel-based alloys S0, S1, and S2 at 800℃ high temperature tensile test are shown in Figure 2. Figure 7 As shown. The number of cracks in Examples S1 and S2 is significantly reduced and the crack length is significantly shortened compared to Comparative Example S0. Among them, the cracks in S2 are particularly small, and only small cracks with the same length along the grain boundary can be observed under high magnification SEM, such as Figure 8 shown.
[0038] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.
Claims
1. A nickel-based alloy, characterized in that: The nickel-based alloy comprises the following components in weight percentage: 0.02%-0.08% of yttrium, 0%-1.54% of niobium, 6.91%-7.10% of chromium, 12.00%-16.45% of molybdenum, and the balance of nickel and inevitable impurities.
2. The nickel-based alloy according to claim 1, characterized in that The nickel-based alloy includes the following components in weight percentage: 0.06%-0.08% of yttrium, 7.10% of chromium, 13.00%-16.45% of molybdenum, and the balance of nickel and inevitable impurities.
3. The nickel-based alloy according to claim 2, characterized in that The nickel-based alloy includes the following components in weight percentage: 0.08% yttrium, 7.10% chromium, 16.45% molybdenum, the balance nickel and inevitable impurities.
4. The nickel-based alloy according to claim 1, characterized in that The nickel-based alloy includes the following components in weight percentage: 0.02%-0.04% of yttrium, 1%-1.54% of niobium, 7.10% of chromium, 12.00%-13.00% of molybdenum, and the balance of nickel and inevitable impurities.
5. The nickel-based alloy according to claim 4, characterized in that The nickel-based alloy includes the following components in weight percentage: 0.02% yttrium, 1.54% niobium, 7.10% chromium, 12.00% molybdenum, the balance nickel and inevitable impurities.
6. The nickel-based alloy according to any one of claims 1 to 5, characterized in that The nickel-based alloy also includes 0.012%-1.6% iron, 0.35%-0.38% silicon, 0.65%-0.67% manganese, and 0.04% carbon by weight.
7. The nickel-based alloy according to any one of claims 1 to 5, characterized in that The impurities are sulfur, boron and phosphorus in a weight percentage of less than 50 ppm.
8. The method for preparing a nickel-based alloy according to any one of claims 1 to 7, characterized in that: The preparation method comprises smelting, homogenization treatment and forging treatment in sequence.
9. The preparation method according to claim 8, characterized in that: The temperature of the homogenization treatment is between 1150°C and 1180°C, and the time of the homogenization treatment is between 2h and 10h.
10. The preparation method according to claim 8, characterized in that: The initial forging temperature of the forging process is 1160°C, and the final forging temperature of the forging process is 1100°C.